IMPLEMENTASI MODEL TWO STAY TWO STRAY (TSTS) DALAM MENINGKATKAN KEAKTIFAN SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA : IMPLEMENTATION OF THE TWO STAY TWO STRAY (TSTS) MODEL TO ENHANCE STUDENT ACTIVENESS IN PANCASILA EDUCATION LEARNING - Irawan, Hendri; Istianah, Anif (Jurnal Al Burhan, 2023)
Pancasila education, as one of the core subjects at the primary and secondary education levels, plays a crucial role in shaping the character and personality of students. However, it is often observed that students are less active and enthusiastic in participating in Pancasila education. This phenomenon can be linked to the lack of attractiveness in the teaching methods, making students less interested in active participation. The predominantly used conventional teaching models tend to be monotonous and less engaging, thus failing to stimulate students' interest and activeness. This research aims to investigate the implementation of the Two Stay Two Stray (TSTS) teaching model in enhancing student activeness in Pancasila education. The TSTS teaching method emphasizes collaboration, idea exchange, and active student involvement in the learning process. The research methodology employed is a qualitative descriptive approach, focusing on a deep understanding of students' behaviors, interactions, and experiences in the learning process. Data analysis is conducted using an inductive approach to identify patterns, findings, and interpretations emerging from the collected data. The results of this research contribute to the development of a teaching model that can increase student participation and engagement in Pancasila education. The TSTS model can be considered an effective alternative to creating a dynamic learning environment that stimulates students' understanding of Pancasila values. This research provides a foundation for improving teaching strategies to advance citizenship education at the Junior High School level. It contributes to a better understanding of the reality of Pancasila education at the Junior High School level, offering a basis for improving teaching strategies and sparking discussions for the development of a more relevant curriculum. The implications of this research can also assist relevant stakeholders in enhancing the quality of citizenship education in schools.